2018
DOI: 10.1002/ece3.4695
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on prey and basal resources exceed that of predators in an experimental community

Abstract: Climate warming alters the structure of ecological communities by modifying species interactions at different trophic levels. Yet, the consequences of warming‐led modifications in biotic interactions at higher trophic levels on lower trophic groups are lesser known. Here, we test the effects of multiple predator species on prey population size and traits and subsequent effects on basal resources along an experimental temperature gradient (12–15°C, 17–20°C, and 22–25°C). We experimentally assembled food web mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 75 publications
(106 reference statements)
3
16
0
Order By: Relevance
“…For instance, when thermal safety margins of insect species are low, increases in temperature substantially reduce the intrinsic rate of population growth (Deutsch et al, 2008;Kingsolver et al, 2013). In such cases, we could expect a more symmetrical response among insect species within a community when exposed to If resources are not limiting (Müller et al, 2015) and predation effects are weaker at higher temperatures (Thakur et al, 2018), we could then make predictions at the insect community level from their population or demographic responses that are related to thermal safety margins. When TE make resources more limiting (Piessens et al, 2009), and higher temperatures enhance demographic rates (Brown et al, 2004), insects that are able to survive with lower resource consumption will have a competitive advantage over others that lack this ability (Ohlberger, 2013).…”
Section: Effec Ts On Te On In S Ec T Communitie Smentioning
confidence: 99%
“…For instance, when thermal safety margins of insect species are low, increases in temperature substantially reduce the intrinsic rate of population growth (Deutsch et al, 2008;Kingsolver et al, 2013). In such cases, we could expect a more symmetrical response among insect species within a community when exposed to If resources are not limiting (Müller et al, 2015) and predation effects are weaker at higher temperatures (Thakur et al, 2018), we could then make predictions at the insect community level from their population or demographic responses that are related to thermal safety margins. When TE make resources more limiting (Piessens et al, 2009), and higher temperatures enhance demographic rates (Brown et al, 2004), insects that are able to survive with lower resource consumption will have a competitive advantage over others that lack this ability (Ohlberger, 2013).…”
Section: Effec Ts On Te On In S Ec T Communitie Smentioning
confidence: 99%
“…abundance of resources but not that of their consumers [10]. While time-related biological events are central in the current understanding of trophic mismatches, differential thermal sensitivity of consumers and resources, such as in their feeding rates, can also trigger warming-induced trophic mismatches [4,23,24]. Moreover, trophic mismatches could also have a spatial component to it [25].…”
Section: Climate Change and Trophic Mismatches In Food Websmentioning
confidence: 99%
“…A major challenge in soils is to track such phenological shifts of species in response to warming given the complexity of the soil habitat and a high density of species [33]. The indication of trophic mismatches in soils in response to climate warming thus mainly comes from studies that have shown differential responses among communities of different trophic levels of brown food webs [4,35,36], potentially also owing to interspecific variation in thermal tolerance between predators and prey communities [37]. These differences in responses are often measured in terms of microbial biomass and soil thermal tolerances Figure 1.…”
Section: Climate Change and Trophic Mismatches In Food Websmentioning
confidence: 99%
“…Our results show that such a pattern was more evident for bacterial communities than their protist predators during and after the extreme heat event. These results indicate that lower trophic groups could also become more vulnerable to climate change than their predators, and it is likely that thermal mismatch across trophic levels depends on both biotic and abiotic contexts (Franken et al., 2018; Thakur et al., 2018). Predator's strategies to minimize thermal stress, such as by remaining inactive or decrease their size in our study may have contributed them with an advantage over prey communities.…”
Section: Discussionmentioning
confidence: 97%